2017
DOI: 10.1016/j.fm.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Fat and fibre interfere with the dramatic effect that nanoemulsified d -limonene has on the heat resistance of Listeria monocytogenes

Abstract: The application of d-limonene in form of nanoemulsion has been proved to reduce dramatically the thermal resistance of Listeria monocytogenes in culture media. The present research shows very promising results on the application in food products. The thermal resistance of L. monocytogenes was reduced 90 times when 0.5 mM nanoemulsified d-limonene was added to apple juice. This is the biggest reduction in the heat resistance of a microorganism caused by an antimicrobial described ever. However, no effect was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…This research expands the findings of the tremendous potential of nanoemulsified oily antimicrobials when combined with thermal treatments, formerly shown on L. monocytogenes [32,33], to Gram-negative bacteria, which are well known to show increased resistance to antimicrobials in comparison to Gram-positive bacteria. This result opens possible uses in the food industry.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…This research expands the findings of the tremendous potential of nanoemulsified oily antimicrobials when combined with thermal treatments, formerly shown on L. monocytogenes [32,33], to Gram-negative bacteria, which are well known to show increased resistance to antimicrobials in comparison to Gram-positive bacteria. This result opens possible uses in the food industry.…”
Section: Discussionsupporting
confidence: 75%
“…As a consequence, the antimicrobial can reach the cell more easily. Maté et al [33] also found that the same effect was shown in a food product, such as apple juice. This finding was also very relevant, since most of the effect found with the combination of heat plus antimicrobials in culture medium is lost when they are applied in food products [34,36].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations